PSYCHOEDUCATION PROCESSES ACADEMIC PROCRASTINATION THROUGH TIME MANAGEMENT - Sholichah, Ima Fitri (Jurnal Konseling Pendidikan Islam, 2025)
This research aims to examine the effectiveness of time management psychoeducation in reducing academic procrastination in high school students. The research method used was A quasi-experimental design with a non-randomized one group pre-test post-test design. The subjects of this research were high school students. Data were collected using the Pure Procrastination Scale and analyzed using statistical tests to see differences before and after the intervention. The research results show that time management psychoeducation can reduce the level of academic procrastination in students. These findings indicate that psychoeducation-based interventions can be an effective strategy in helping students manage their time better and reduce the habit of procrastinating on academic tasks.